Effects of amorphous aluminum hydroxide on chloride immobilization in cement-based materials. (20th January 2020) - Chen, Pian; Ma, Baoguo; Tan, Hongbo; Liu, Xiaohai; Zhang, Ting; Qi, Huahui; Peng, Yi; Yang, Qi; Wang, Jingran
Highlights: AAH enhanced the chloride immobilization capacity in cement-based materials. AAH hindered the cement hydration but hastened the formation of Kuzel's salt. AAH refined the pore structure but reduced the compressive strength. Abstract: This study investigated the effects of amorphous aluminum hydroxide (AAH) on chloride ions immobilization ability of cement-based materials. Paste samples with different dosages of AAH were prepared, and the chloride binding capacity was examined. Hydrates at the age of 7 d and 28 d were analyzed by X-ray diffraction (XRD), thermo-gravimetric analysis (TGA), and Nuclear Magnetic Resonance (NMR). Pore structure was also evaluated by mercury intrusion porosity (MIP). Results revealed that addition of AAH retarded the cement hydration, refined the pore structure, and enhanced the immobilization ability of chloride ions in cement-based materials. The increase in immobilized chloride ratios (ICR) was related to three aspects: a) the migration resistance was strengthened by the refined pore structure; b) chemical binding ability was increased because of the increased content of Kuzel's salt in hydrates; c) the physical adsorption ability was weakened by the reduced amount of C-S-H gel in hydrates due to the retarding effect of AAH.